A Fiber Supercapacitor with High Energy Density Based on Hollow Graphene/Conducting Polymer Fiber Electrode. Issue 19 (22nd March 2016) - Qu, Guoxing; Cheng, Jianli; Li, Xiaodong; Yuan, Demao; Chen, Peining; Chen, Xuli; Wang, Bin; Peng, Huisheng
Abstract : A hollow graphene/conducting polymer composite fiber is created with high mechanical and electronic properties and used to fabricate novel fiber‐shaped supercapacitors that display high energy densities and long life stability. The fiber supercapacitors can be woven into flexible powering textiles that are particularly promising for portable and wearable electronic devices.